Meandry prawne autoryzacji - Sobczak, Jacek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
Press law protects the informers of journalists and the persons who collaborate with them and give interviews. This protection not only prohibits the disclosure of details which could help identify the informers, but also imposes other requirements on the journalists with respect to all these people who have decided to speak to them or be interviewed. Particular requirements apply to the issue of authorization. The fundamental function of authorization is to protect the contents of a statement which is treated as an unprotected good by the regulations of copyright law or the civil code with respect to personal interests. At present, authorization is the only legal instrument enabling the author of a statement for publication to ensure its integrity and true meaning. The abandonment of authorization in the system of legal institutions would deprive the persons providing information of protection of their personal interest, i.e. the right to free speech.